Prevalence of metabolic syndrome in non-obese newly detected Type-2 diabetes Mellitus (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: The metabolic syndrome is driving twin global epidemics; type 2 diabetes mellitus and cardiovascular disease. There is an overwhelming moral, medical, and economic imperative to identify those individuals with metabolic syndrome. Regarding this issue, non obese individuals are given less attention and ultimately situation becomes grievous therefore.Objective: To assess the prevalence of metabolic syndrome in nonobese newly detected type 2 DM patient. Method: This cross sectional analytical study was carried out in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Total 209 cases (165 male & 44 female) were selected from BIRDEM. Statistical analysis and data management were carried out using the SPSS (Version 12.0).Result: In this study, prevalence rates of metabolic syndrome were 60.3% (53.3% male, 86.4% female), 58.9% (57.0% male, 65.9% female) and 26.3% (15.8% male, 65.9% female) according to modified National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III), modified WHO & IDF criteria respectively.Conclusion: Prevalence of metabolic syndrome in non-obese newly detected Type 2 DM is very high & Prevalence of metabolic syndrome in non-obese newly detected Type 2 DM found significantly higher in female than male. Adequate realistic steps of preventive strategy are of urgent need to combat this high prevalence of metabolic syndrome in non-obese diabetic people.